Déterminants psychologiques des stratégies de coping des arbitres de football - Louvet, B.; Campo, M.; André, A. (2015)
Referees, as well as athletes, constantly have to cope with high stressful conditions. This study aims at examining the direct and indirect effects of situational (i.e., perceived control and perceived importance of the game, intensity of cognitive and somatic anxiety, and intensity of self-confidence) and dispositional (i.e., trait anxiety, self-esteem, optimism, pessimism, and perfectionism) determinants on soccer referees` coping strategies. Soccer referees (N = 222; M = 32.7 years), officiating from professional (N = 66) to amateur (N = 156) level participated in this study. A structural equation model revealed that coping strategies of soccer referees are significantly predicted by the perceived importance of the game, the intensity of cognitive and somatic anxiety. The intensity of cognitive anxiety represents the situational determinant which alone mediates the relation between the dispositional variables (i.e., trait anxiety and perfectionism) and coping (problem- and emotion-focused coping). Finally, perfectionism constitutes the only dispositional variable that directly predicts the coping strategies used by soccer referees. The study suggests a deeper investigation of perfectionism and direction of anxiety in order to provide further knowledge on the coping process with sport referees.